Peace Education: Innovation in Islamic Education Policy in the Conflict Region of Southern Thailand - Muharrani; Azni Aisyah; Ilham Kurnia (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Southern Thailand has experienced a protracted ethno-religious conflict rooted in the 1909 annexation of the Sultanate of Patani, resulting in systematic marginalization of the Malay-Muslim minority and militarization of Islamic educational institutions. This study examines innovations in Islamic education policy aimed at transforming this entrenched conflict through peace education. Employing a systematic literature review methodology, this research analyzes peer-reviewed sources and policy documents published between 2010 and 2024 to investigate three core dimensions: the historical dynamics of conflict and their educational implications, the conceptual foundations of peace education within Islamic pedagogical frameworks, and the implementation outcomes of policy innovations—particularly the mandatory Peace Study curriculum at Fatoni University. The findings reveal that colonial assimilationist policies and post-2004 securitization fundamentally altered Islamic schools from cultural preservation centers into objects of state suspicion. However, recent innovations demonstrate incremental policy learning, integrating core Islamic values of salām (peace), rahmatan lil alamin (mercy to all creation), and tasamuh (tolerance) with Western conflict transformation theories. The mandatory Peace Study at Fatoni University represents the first institutionalized peace education requirement in Thailand, combining theological grounding with practical pedagogical approaches. Despite significant structural advances, sustainability remains constrained by political volatility, institutional capacity deficits, and persistent trust gaps between state institutions and Malay-Muslim communities. This study concludes that sustainable peacebuilding requires not merely curriculum innovation but comprehensive political reconciliation, community-legitimized implementation, and culturally grounded educational reform that respects Patani's collective identity within Thailand's national narrative.